A COMPARATIVE STUDY OF WRITING COMPETENCE BETWEEN EXTROVERT AND INTROVERT STUDENTS AT MTS MIFTAHUL ULUM SUMBERMANJING WETAN MALANG - Joko Wibowo (English Language Teaching Journal, 2022)
The purpose of this research was to find out the significant difference on writing competence between extrovert and introvert students at the second grader of Junior High School Miftahul Ulum Sumbermanjing Wetan Malang. There were 25 students as the samples chosen by using Purposive Sampling. This research used quantitative approach and the type of the research was a causal comparative. In conclusion, there is a significant difference on students writing competence between extrovert and introvert students. The result showed that introvert students better than extrovert students in writing competence. Because the result of this research was in line with the theory stated that introvert is better in writing skill, so the researcher gives suggestions in order to the teachers apply different method, technique or strategy in teaching writing that is suitable for both of them. So, it is not only focus to introvert students who tend to be superior in writing but also to extovert students too Keywords: Comparative Study, Extrovert, Introvert, Writing Competence.